2023
DOI: 10.21037/atm-22-6475
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and strategies for recovery quality, postoperative pain, and recurrent fractures between percutaneous kyphoplasty and percutaneous vertebroplasty in elderly patients with thoracolumbar compression fractures: a retrospective comparative cohort study

Abstract: Background With the increase of clinical cases and the improvement of operation, we found that recurrent fracture of the adjacent vertebral body is a common long-term complication of percutaneous kyphoplasty (PKP). However, the mechanism of re-fracture of adjacent vertebrae after PKP has not been unified. Therefore, through retrospective study, this paper discussed the risk factors and countermeasures affecting the quality of rehabilitation, postoperative pain and recurrent fracture in elderly PKP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Thirty-seven patients (13.8%) experienced vertebral refracture. We compared the data between the refractured group and the non-refractured group to determine the significant risk factors identified previously [ 11 , 14 , 17 ]. Bone cement leakage was not observed in 269 patients and was not analyzed in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty-seven patients (13.8%) experienced vertebral refracture. We compared the data between the refractured group and the non-refractured group to determine the significant risk factors identified previously [ 11 , 14 , 17 ]. Bone cement leakage was not observed in 269 patients and was not analyzed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Although the advantages of PKP have been well demonstrated, vertebral refractures after PKP have been reported at rates ranging from 10 to 29.4%, affecting both adjacent and distant vertebrae [ 8 – 10 ]. There are many risk factors for refractures after PKP [ 11 ], and sagittal spinal imbalance has been acknowledged as the predominant contributor in previous studies [ 8 , 12 – 14 ]. In our prior research, however, we observed a high prevalence of osteoporosis among patients aged > 50 years who underwent spinal surgery, especially among those primarily diagnosed with degenerative scoliosis [ 15 ].…”
Section: Introductionmentioning
confidence: 99%